Systematics of Paraleucopis Malloch with proposal of Paraleucopidae, a new family of acalyptrate Diptera - Wheeler, Terry A.; Sinclair, Bradley J. (Zootaxa, 2019)
Paraleucopidae Wheeler fam. nov. is proposed for the previously unplaced New World genera Paraleucopis Malloch, Mallochianamyia Santos-Neto and Schizostomyia Malloch and undescribed Australian species. A key to genera of Paraleucopidae is provided. Paraleucopis is revised and includes nine species: P. auripes Wheeler & Sinclair sp. nov. (type locality: Andalgala, Argentina); P. bispinosa Wheeler & Sinclair sp. nov. (type locality: Socos, Coquimbo, Chile); P. boharti Wheeler & Sinclair sp. nov. (type locality: Andalgala, Argentina); P. boydensis Steyskal (type locality: nr. Palm Desert, California, USA); P. corvina Malloch (type species of genus; type locality: New Mexico, USA); P. mexicana Steyskal (type locality: Kino Bay, Mexico); P. nigra Wheeler & Sinclair sp. nov. (type locality: Portal, Arizona, USA); P. paraboydensis Wheeler & Sinclair sp. nov. (type locality: Willis Palms Oasis, California, USA); P. saguaro Wheeler & Sinclair sp. nov. (type locality: Usery Mtn Park, Arizona, USA). A key to the species of Paraleucopis is provided. The distribution of Paraleucopis is disjunct, with six species in the western United States and northwestern Mexico and three species in northern Chile and northern Argentina.                The sister group and superfamilial assignment of the Paraleucopidae cannot be established based on current knowledge although the family has affinities to some families of the Asteioinea sensu J.F. McAlpine. A well-supported hypothesis on the relationships of the families of the Acalyptratae will be required before the sister group relationships of Paraleucopidae can be determined.